Minor Physical Anomalies in Bipolar Disorder—A Meta-Analysis - Varga, Eszter; Hajnal, András; Soós, Alexandra; Hegyi, Péter; Kovács, Dóra; Farkas, Nelli; Szebényi, Júlia; Mikó, Alexandra; Tényi, Tamás; Herold, Róbert (Frontiers in Psychiatry, 2021)
Objectives: Minor physical anomalies (MPAs) may reflect basic neurobiological features underlying bipolar disorders, as they are nonsignificant faults of morphogenesis. There are several research about the presence of MPAs in bipolar disorders, however the results in favor of a neurodevelopmental basis for the disease is controversial. The aim of our meta-analysis was to assess the standardized weighted mean effect sizes of MPAs in bipolar disorders (BPD), and to investigate if MPAs may be found predominantly in the head and facial regions in patients compared to healthy controls (HC). Methods: Four studies, involving 155 patients with BPD, and 187 HC, were involved in the analysis after searching the literature. For the investigation of MPAs in the periferial (MPA-P) and in the head and facial regions (MPA-FC) two studies involving 121 BPD patients, and 133 HC passed the inclusion criteria. Results: The number of the MPAs in the BPD group were significantly higher compared to HC. Another important finding of the present study is that BPD patients’ MPA-P scores do not significantly differ from those of the HC. In contrast, BPD patients’ MPA-CF scores were found to be significantly higher compared to HC subjects. Conclusions: Our findings suggest an early insult during the development of the brain in BPD